SF6/Ar plasma textured periodic glass surface morphologies with high transmittance and haze ratio of ITO:Zr films for amorphous silicon thin film solar cells. (July 2015) - Hussain, Shahzada Qamar; Kwon, Gi Duk; Ahn, Shihyun; Kim, Sunbo; Park, Hyeongsik; Le, Anh Huy Tuan; Shin, Chonghoon; Kim, Sangho; Khan, Shahbaz; Raja, Jayapal; Balaji, Nagarajan; Velumani, S.; et al.
Abstract: We report various SF6 /Ar plasma textured periodic glass surface morphologies with high transmittance, haze ratio, and root mean square (rms) roughness of ITO:Zr films for amorphous silicon thin film solar cells (a-Si TFSCs). SF6 /Ar plasma textured glass surface morphologies contain micro- and nano-textured features that help to scatter the light in visible and near infra-red (NIR) wavelength regions. We designed the textured glass surface morphologies with big square craters to smaller pyramids for various glass etching times from 30 to 75 min. Magnetron sputtered ITO:Zr (∼210 nm) films were deposited on textured glass surface morphologies and showed higher transmittance and haze ratio of 88.48% and 77.61%, respectively, in the visible-NIR (400–1100 nm) wavelength region. The sheet resistance and resistivity of ITO:Zr films decreased with the increase of etching time, due to high rms roughness and better step coverage. A passivation AZO (30 nm) layer was added to the ITO:Zr films, due to its better stability against hydrogen plasma exposure. The ITO:Zr/AZO films were employed as a front TCO layer and the current density–voltage (J–V) characteristics of a-Si TFSCs increased by light scattering effect, without any reduction in either the open circuit voltage (VOC ) or the fill factor (FF). Relative to flat glass substrate, JSC and the efficiency of a-Si TFSCs were enhanced by 7.51% and 19.39%, respectively, for textured glass surface morphology. Highlights: Various textured SF6 /Ar plasma based glass surface morphologies are presented. ITO:Zr films deposited on textured glass showed high transmittance and haze ratio. Micro- and nano-size features of textured glass can scatter light in visible-NIR region. Decrease in sheet resistance of ITO:Zr films was due to high rms and step coverage. JSC of thin film solar cells was enhanced due to light scattering effect.